A Measure of Tolerance: Public Attitudes on Sentencing Enhancements for Old and Juvenile Prior Records. Issue 2 (3rd April 2018) - Hester, Rhys; Roberts, Julian V.; Frase, Richard S.; Mitchell, Kelly
ABSTRACT: Sentencing policies routinely assign harsher punishment on repeat offenders, yet we know little about public attitudes toward recidivist sentencing premiums—beyond the predictable finding that people are more punitive when the offender is a recidivist. We conducted a survey to explore public reaction to two key inquiries: (1) whether older priors should carry less weight at new sentencing hearings and (2) whether juvenile priors should be counted at adult sentencing hearings. Many sentencing guidelines systems count all prior convictions forever and juvenile priors are almost always included. Results indicate that in contrast to current practice in U.S. guidelines jurisdictions, the public significantly discounts older priors, and favors disregarding at least some juvenile priors. Policy consequences are discussed.